Menelusuri Jejak UGM dalam Gerakan Reformasi Indonesia dari Sumber Arsip Statis Khazanah Arsip UGM - Musliichah Musliichah (Arsip Universitas Gadjah Mada, 2017)
Events reforms brought major changes in the history of the Indonesian nation can be used as a learning process. Studying the past can be a learning process. History will be more effective as a learning process where not only read but studied and researched. UGM as universities struggle born in the midst of a revolution becomes part of the Indonesian nation struggles tool. UGM called to participate in the reform movement during the struggle. Research based on Arsip UGM Archives can be described what happened reform movement in the UGM; elements that are involved in it (student, lecture, UGM institutions and UGM units, and employees); and forms of reform activities like demonstrations, research, organization of scientific forums, statement, recommendations, and media announcement.